CONSERVATION CONCEPT OF OLD KAMPUNG THROUGH THE APPLICATION OF SUSTAINABLE DEVELOPMENT PRINCIPLES AT KAMPUNG SURABAYAN, KEDUNGDORO DISTRICT, SURABAYA - Anindita Ramadhani; Erina Wulansari; Putri M. Mawarsari; Johan Silas (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2014)
Kampung Surabayan is one of old kampungs in Surabaya, Indonesia, that has some potentials which can be developed as a sustainable kampung by balancing the environmental, socio-cultural, and economic aspects. In environmental aspect, Kampung Surabayan already has a good management based on various achievements from Green and Clean Competition (an eco-friendly settlement competition) and Safe Kampung Competition which held by Surabaya Government. The historical potential and cultural heritage, cooperative kampung’s residents, unique “kampung” traditions such as